Associations Between Inflammatory and Immune Response Genes and Adverse Respiratory Outcomes Following Exposure to Outdoor Air Pollution: A HuGE Systematic Review. Issue 4 (14th November 2013) - Vawda, Seema; Mansour, Rafif; Takeda, Andrea; Funnell, Paula; Kerry, Sally; Mudway, Ian; Jamaludin, Jeenath; Shaheen, Seif; Griffiths, Chris; Walton, Robert
Abstract: Variants of inflammatory and immune response genes have been associated with adverse respiratory outcomes following exposure to air pollution. However, the genes involved and their associations are not well characterized, and there has been no systematic review. Thus, we conducted a review following the guidelines of the Human Genome Epidemiology Network. Six observational studies and 2 intervention studies with 14, 903 participants were included (2001–2010). Six studies showed at least 1 significant gene-pollutant interaction. Meta-analysis was not possible due to variations in genes, pollutants, exposure estimates, and reported outcomes. The most commonly studied genes were tumor necrosis factor α ( TNFA ) ( n = 6) and toll-like receptor 4 ( TLR4 ) ( n = 3). TNFA –308G>A modified the action of ozone and nitrogen dioxide on lung function, asthma risk, and symptoms; however, the direction of association varied between studies. The TLR4 single-nucleotide polymorphisms rs1927911, rs10759931, and rs6478317 modified the association of particulate matter and nitrogen dioxide with asthma. The transforming growth factor β1 ( TGFB1 ) polymorphism –509C>T also modified the association of pollutants with asthma. This review indicates that genes controlling innate immune recognition of foreign material ( TLR4 ) and the subsequent inflammatory response ( TGFB1, TLR4 ) modify the associations of exposure to air pollution with respiratory function. The associations observed have biological plausibility; however, larger studies with improved reporting are needed to confirm these findings.